A Critical Review of Cooperation Systems in Libraries and Information Centers - Hamidreza Radfar; Maryam Salami; Solmaz Noori (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Libraries and information centers always try to provide the best and most appropriate answers to their clients’ questions and needs. Due to the increasing and diverse variety of information resources, many libraries do not the capacity to provide these resources and make them accessible. Narges Neshat considers cooperation between libraries and information centers as a solution to expand the library’s access to a variety of information resources to meet the needs of their clients. Moreover, by publishing the book “Collaborative Systems in Libraries and Information Centers”, the author has addressed this issue. This resource, which can be considered as an educational resource for students of information and knowledge science and an applied source for specialists and professionals in this science, was critically examined in a descriptive-analytical manner. In this article, after introducing the book, its author and publisher, the structure of the book is mentioned, and then the book is reviewed in both form and content terms. This work is a specialized book in the subject of cooperation between libraries and information centers and has an appropriate scientific level. The most important weakness of this work is the lack of applied aspects; a few parts of this book are not specialized, and the resources used for this work are old.